Nanoparticle Formula Optimization of Juwet Seeds Extract (Syzygium cumini) using Simplex Lattice Design Method - Yohanes Juliantoni; Wahida Hajrin; Windah Anugrah Subaidah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
Diabetes is a degenerative disease whose numbers continue to increase from year to year. Treatment with oral antidiabetic drugs can cause harmful side effects for patients. One of the plants that can be used for diabetes therapy is juwet (Syzygium cumini L.). Flavonoid compounds of juwet seed is easily oxidized and hydrolyzed in intestinal fluids with low absorption. This problem can be overcome by forming nanoparticle of juwet seed extract. The aims of this study was to obtain the formula for juwet seed nanoparticles. Nanoparticle of juwet seed extract made by ionic gelation method with chitosan and Na-TPP polymers which are varied. The formula optimization design in this study was determined using a simplex lattice design by 3 variations of materials based on the parameters %entrapment efficiency, %transmittant, particle size, polydisperse index, and zeta potential. The results showed that the yield of duwet seed extract was 7,44%. Juwet seed ethanolic extract contains 3.33 mg of quercetin per 1 g of extract. Based on the desirability value approach, the optimum formula was produced with an extract composition of 1.650 mL; chitosan 0.500 mL; and Na-TPP 0.010 mL can give optimal results with a desirability value of 0.772 which results in the criteria of 63.66% entrapment efficiency; 50.56% transmittant; 615,833nm particle size; 0.620 PDI; and zeta potential of +13.89 mV. Juwet seeds extract can be formulated into the form of nanoparticles. To get better parameters, it is advisable to optimize the mixing time and mixing speed in the ionic gelation method.